Synthesis, spectroscopic characterization and antimicrobial studies of mercury(II) complexes of thiolates. Issue 1 (2009) - Rabbani Rabbani, Ghulam Ghulam; Isab Isab, Anvarhusein A. Anvarhusein A.; Al-Arfaj Al-Arfaj, Abdul Rahman Abdul Rahman; Ahmad Ahmad, Saeed Saeed; Saleem Saleem, Muhammad Muhammad; Hameed Hameed, Abdul Abdul; Akbar Akbar, Erum Erum
Abstract : Mercury(II) complexes of thiolates having the general formula [Hg(RS)Cl2 ] − and [Hg(RS)2 ] have been prepared and characterized by IR and NMR ( 1 H and 13 C) spectroscopy (RSH = 2-aminoethanethiol hydrochloride (Aet), cysteine (Cys), thiosalicylic acid (Ts) and 2-mercaptonicotinic acid (Mnt)). The spectral data suggests that the coordination of thiolates to mercury(II) occurs through the sulfur as indicated by the absence of S–H vibrations in IR and significant downfield shifts in the C–S resonance in 13 C NMR. However, in Mnt complexes, coordination through both sulfur and nitrogen is indicated. Antimicrobial activities of the complexes were evaluated by minimum inhibitory concentration and the results showed that the complexes exhibited a wide range of activities against gram-negative bacteria ( E. coli, P. aeruginosa ), while moderate activity was observed against a mold, P. citrinum .